A Study on the Energy Absorption Performance of Mine Grooved Conical Tube Energy Absorption Components - Ziyang Li; Xiaochun Xiao; Jun Xu; Bin Sun (Buildings)
When rockbursts occur, hydraulic support is prone to impact failure, which leads to severe casualties and economic losses. To improve the performance of hydraulic support structures under impact loading, a grooved conical tube is designed as an energy absorption device to avoid hydraulic columns being destroyed. The performance of the grooved conical tube during deformation is studied using simulation, considering the wall thickness, cone angle and number of grooves. The equivalent axial load of the grooved conical tube component is derived by studying the energy dissipation path. And the grooved conical tube’s structure is optimized. The results show that the Y3-5-10 (cone angle: 3°; number of grooves: 5; wall thickness: 10 mm) grooved conical tube shows excellent performance among the twenty-seven types of structures. In addition, the equivalent axial load prediction formula for the grooved conical tube has a high prediction accuracy. Furthermore, after multi-objective optimization, the mean square error is decreased by 20.6%, and the effective energy absorption is increased by 6.0%, which is able to make the energy absorption process more stable. Compared with widely used corrugated square tubes, the effective deformation distance of the grooved conical tube is increased by 27.2%, and the effective energy absorption is increased by 37.1%. The grooved conical tube has advantages in its effective deformation distance and effective energy absorption. These results are expected to provide sufficient time for the opening of the support column’s relief valve and to enhance the impact resistance of the hydraulic support, which is highly important for the prevention of rockbursts.